Influenza Vaccination Among Patients Undergoing Treatment for Rheumatological Disorders: Awareness, Vaccination Rates, and Influencing Factors - Akyuz, Merve Sari; Akyuz, Bülent; Keskin, Olgun; Sezer, Ilhan (Archives of Rheumatology, 2025)
Background/Aims: Patients with autoimmune inflammatory rheumatic diseases (AIIRDs) are particularly vulnerable to infections as a result of their underlying autoimmune conditions. This vulnerability is further exacerbated by immunosuppressive treatments and associated comorbidities. This study aims to evaluate influenza vaccination rates, hesitancy, and awareness among this patient population. Materials and Methods: This descriptive study included patients with AIIRD receiving treatment at rheumatology and pulmonary medicine outpatient clinics. Between January and April 2024, a questionnaire was administered to assess influenza vaccination rates, knowledge, and attitudes. Results: Of the patients, 34.3% had received at least 1 influenza vaccination, while only 13% were vaccinated annually. Additionally, 62.2% recognized that they were at risk for influenza infection due to their current illnesses and medications and believed that they should be vaccinated. However, 59.2% had not received any professional information about the influenza vaccine. Only 38.2% were aware that vaccination was available free of charge for their condition. Older age, prolonged medication use, extended duration since diagnosis, presence of comorbidities, awareness of influenza risk, and receiving information about vaccination were all significantly associated with having received at least 1 influenza vaccination. No statistical relationship was observed between the type of rheumatic disease and vaccination (P= .7803). Patients relying on social media, TV, or internet sources demonstrated greater vaccine hesitancy (P < .0001). Awareness of vaccination recommendations was significantly associated with medication type (P < .0001). Hesitancy was reported by 38.7% of all patients and 48% of unvaccinated patients, influenced by negative experiences during the COVID-19 vaccination process. Conclusion: Influenza vaccination coverage among patients with AIIRD remains suboptimal. Physician reminders during routine visits could enhance vaccination rates. Health authorities might consider implementing pop-up alerts in clinical systems to prompt physicians to recommend vaccination when prescribing immunosuppressive medications.